Motor activity recorded in the unprepared colon of healthy humans. Issue 5 (November 1995) - Lémann, M; Flourié, B; Picon, L; Coffin, B; Jian, R; Rambaud, J C
Abstract : A manometric method was developed to study the motor activity in the unprepared human colon, and the results in eight healthy subjects were compared with those obtained in the same subjects after bowel cleansing with a non-absorbable solution containing polyethylene glycol 4000 (PEG). A tube assembly (4.5 m long, 12 lumen) was introduced through the nose and passed through the gastrointestinal tract. Two manometric recordings were performed one month apart, one without any preparation and the other after bowel cleansing with PEG. There was no obvious qualitative difference between the recordings performed in the uncleansed and PEG cleansed colon. Moreover, in the unprepared colon motility indices were close to those measured in the cleansed colon. The number of high amplitude propagated contractions (mean (SEM)) was, however, higher in the cleansed colon (8.6 (2.8) v 5.4 (1.8)/subject/9 h in the unprepared colon; p < 0.04). It is concluded that in healthy subjects taking a regular diet, motor activity is not different between the uncleansed and cleansed colon with PEG, except for the high amplitude propagated contractions, which occur more frequently in the cleansed colon.